2014
DOI: 10.1097/scs.0000000000000841
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Plexus Injury

Abstract: The brachial plexus is a series of nerves formed by roots of cervical segments 5 to 8 (C5-C8) as well as the first thoracic nerve (T1). It functions to provide sensation and motor innervation to the skin and muscles of the chest and upper limb. It does so through different segments: roots, trunks, divisions, and cords. Injuries to the brachial plexus occur relatively frequently and are due mainly to traumatic accidents that lead to traction or compression of the nerve roots. When considering the etiology and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 53 publications
0
10
0
12
Order By: Relevance
“…Moreover, a reporting bias should be considered in the epidemiology of BPIs related to sport activities. Indeed, almost all studies reported the incidence and prevalence of traumatic BPIs that required surgical treatment [54]. Several lesions of brachial plexus showed a less dramatic involvement of nerve structures, with neuroapraxia and partial axonotmesis.…”
Section: Epidemiology Of Bpis and Their Relevance In Sport Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a reporting bias should be considered in the epidemiology of BPIs related to sport activities. Indeed, almost all studies reported the incidence and prevalence of traumatic BPIs that required surgical treatment [54]. Several lesions of brachial plexus showed a less dramatic involvement of nerve structures, with neuroapraxia and partial axonotmesis.…”
Section: Epidemiology Of Bpis and Their Relevance In Sport Medicinementioning
confidence: 99%
“…The timing of surgical treatment has been extensively discussed in scientific literature [36,54]. Some BPIs (i.e., gunshots injuries) are associated to vascular injuries or open lesions (i.e., cut lesions) and require acute surgical treatment [90].…”
Section: Surgerymentioning
confidence: 99%
“…En los últimos años ha disminuido debido al entendimiento de la enfermedad y el cuidado durante el trabajo de parto. 1,3,5,6 El principal factor de riesgo para esta alteración es la distocia de hombros, que puede provocar tracción del plexo braquial. Otros factores asociados son: utilización de fórceps, macrosomía, tiempo de parto prolongado, presentación pélvica, desproporción cefalopélvica, multiparidad y diabetes gestacional.…”
Section: Introductionunclassified
“…Otros factores asociados son: utilización de fórceps, macrosomía, tiempo de parto prolongado, presentación pélvica, desproporción cefalopélvica, multiparidad y diabetes gestacional. [1][2][3]6,7 Aunque en la bibliografía se indica que 90% de los casos se cura de forma espontánea (3 meses a 2 años), se estima que entre 20-30% de los niños afectados permanecen con déficit residual. 1,[3][4][5]…”
Section: Introductionunclassified
“…Many of the contemporary series are evaluating functional recovery of patients operated for BPI, regardless of the cause of the injury, mainly due to rarity of these injuries ( 20 - 22 ). Missile injuries of the brachial plexus occur almost inextricably with war, while also carrying along specific associated injuries, and difficulties in diagnosing the injury and estimating the extension and level of severity.…”
Section: Introductionmentioning
confidence: 99%